2022
DOI: 10.1186/s13148-022-01327-2
|View full text |Cite
|
Sign up to set email alerts
|

Integrated single-cell RNA-seq and DNA methylation reveal the effects of air pollution in patients with recurrent spontaneous abortion

Abstract: Background Maternal air pollutants exposure is associated with a number of adverse pregnancy outcomes, including recurrent spontaneous abortion (RSA). However, the underlying mechanisms are still unknown. The present study aimed to understand the mechanism of RSA and its relationship with air pollution exposure. We compared data of decidual tissue from individuals with induced abortions and those with RSA by bulk RNA sequencing (RNA-seq), reduced representation bisulfite sequencing (RRBS), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…All in all, in the new era of biomedicine, more novel techniques and related applications will help us to get more discoveries and breakthroughs. [151][152][153] In fact, a next-generation sequencing from RNA-seq to scRNA-seq, in particular combined with GWAS and/or DNA methylation analysis, [154][155][156] will identify novel susceptibility loci, reveal molecular characteristics and comprehensive cellular and molecular mechanisms. Different from whole-exome sequencing, [157,158] this new targeted and next-generation sequencing at the SC level, [159][160][161] that is scRNA-seq, [162][163][164] will definitely help to screen, diagnose, and treatment of CHD, [165] COVID, [166] and others.…”
Section: Cavdmentioning
confidence: 99%
“…All in all, in the new era of biomedicine, more novel techniques and related applications will help us to get more discoveries and breakthroughs. [151][152][153] In fact, a next-generation sequencing from RNA-seq to scRNA-seq, in particular combined with GWAS and/or DNA methylation analysis, [154][155][156] will identify novel susceptibility loci, reveal molecular characteristics and comprehensive cellular and molecular mechanisms. Different from whole-exome sequencing, [157,158] this new targeted and next-generation sequencing at the SC level, [159][160][161] that is scRNA-seq, [162][163][164] will definitely help to screen, diagnose, and treatment of CHD, [165] COVID, [166] and others.…”
Section: Cavdmentioning
confidence: 99%
“…Adverse pregnancy and birth outcomes (APBOs) including miscarriage, Low birth weight (LBW), preterm birth (PTB), sepsis, and intrauterine growth restriction (IUGR) are major public health problems and have been linked with a high risk of mortality and morbidities during both the neonatal period and later in life [ 1 – 4 ]. The majority of these APBOs are associated with maternal exposure to genetic and environmental factors during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al conducted a comprehensive analysis of decidual tissue data obtained from individuals who underwent induced abortions and those with recurrent spontaneous abortion (RSA). This analysis involved the use of bulk RNA sequencing (RNAseq), reduced representation bisul te sequencing (RRBS), and single-cell RNA sequencing (scRNA-seq) [13]. The ndings of this study revealed that a thorough understanding of the cellular and molecular mechanisms underlying RSA can be achieved, with a particular focus on the potential impact of IGF2BP1 promoter methylation on pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%